Is Kidney Stiffness Measured Using Elastography Influenced Mainly by Vascular Factors in Patients with Diabetic Kidney Disease?. (September 2018) - Bob, Flaviu; Grosu, Iulia; Sporea, Ioan; Timar, Romulus; Lighezan, Daniel; Popescu, Alina; Sirli, Roxana; Buzas, Roxana; Petrica, Ligia; Munteanu, Mircea; Schiller, Adalbert
Studies published so far using ultrasound-based elastography in the kidneys, lack to prove a clear relationship between kidney shear wave speed (KSWS) and renal disease progression. Taking into account that the kidney is a highly vascularized organ, the present study aims to find a relationship between KSWS and vascular factors (blood pressure [BP], arterial stiffness). Our study included 38 diabetic kidney disease patients (mean age 56.52 ± 16.12 years, 19 female, 19 male). KSWS, an indicator of renal stiffness, was measured using point Shear Wave Elastography (pSWE; Siemens Acuson S2000). In every patient, we recorded BP, and we measured aortic augmentation index (AAI) and brachial pulse wave velocity (PWV), using oscillometry. We found statistically significant indirect correlations of KSWS with indicators of arterial stiffness, such as PWV ( r = –.41, p = .036), and AAI ( r = –.37, p = .031). We found also an indirect correlation of KSWS with diastolic BP ( r = –.65, p = .02) and systolic BP ( r = –.54, p = .008). We found no correlation of KSWS with estimated glomerular filtration rate (eGFR), urinary albumin/creatinine ratio, stage of diabetic retinopathy, or glycated hemoglobin. Our study shows that high BP and the progression of arteriosclerosis (high PWV and AAI), leads to a decrease of renal stiffness. Thus, it seems that KSWS is influenced by renal blood flow, rather than other factors, such as albuminuria or chronic kidney disease stage.